Numerical treatment with Lobatto-IIIa scheme magneto-thermo-natural convection flow of casson nanofluid (MoS₂ − Cu/SA) configured by a stretching cylinder in porous medium with multiple slips - Ahmad, Farooq (2022)
In biological instruments, medicines and agriculture, the agglomeration of nanofluids and biotechnological mechanisms can offer significant advantages. The nanofibers, nanowires, droplets are more useful in the field of nanotechnology. There is a significant demand for nanotechnology and one can expect that the future of these materials is very bright. Due to the different shapes and sizes of the nanomaterials, it is exemplified into various types. In one of them are carbon nanotubes (CNTs). These nanotubes are carbon allotropes. Carbon nanotubes are more practiced in the field of energy storage, optics, thermal stability, nanotubes transistors, and electromagnetic interference and in many areas. Keeping in such practical applications of nanotubes and nanofluid, we have scrutinized the magneto Casson nanofluid flow past a cylinder with carbon nanotubes (MWCNT and SWCNT). Here the sodium alginate is utilized as a regular fluid and nanoparticles MoS2 and Cu are dispersed in it. The impacts of multi slip behavior are considered in the presence of nonlinear thermal radiation. Multi degree governing flow equations are remodeled by similarity transformation and then tackled via shooting algorithm with Lobatto-IIIa formula. The physical flow behaviors of interesting parameters against velocity and temperature field are elaborated in Figures using Matlab software. Results indicate that flow of fluid is decline with fluid parameter. Further, volume fraction of nanoparticles reduces the temperature. The study is relevant to efficient thermal transportation in heat exchangers and electronic appliances.